A Novel Deceptive Jamming Approach for Hiding Actual Target and Generating False Targets. (7th April 2021) - Mehmood, Shahid; Malik, Aqdas Naveed; Qureshi, Ijaz Manssor; Khan, Muhammad Zafar Ullah; Zaman, Fawad
Abstract : Deceptive jamming is a popular electronic countermeasure (ECM) technique that generates false targets to confuse opponent surveillance radars. This work presents a novel approach for hiding the actual target while producing multiple false targets at the same time against frequency diverse array (FDA) radar. For this purpose, the modified FDA radar is assumed to be mounted on the actual aircraft. It intercepts the opponent's radar signals and transmits back to place nulls in the radiation pattern at the desired range and direction to exploit FDA radar's range-dependent pattern nulling capability. The proposed deceptive jammer produces delayed versions of the intercepted signals to create false targets with multiple ranges to confuse the opponent's radar system. The novel mathematical model is proposed whose effectiveness is verified through several simulation results for different numbers of ranges, directions, and antenna elements.